A reappraisal of the taxonomy of Neotropical Sialidae (Insecta: Megaloptera): with the description of a new genus from Cuba - Ardila-Camacho, Adrian; Rivera-Gasperín, Sara Lariza; Martins, Caleb Califre; Contreras-Ramos, Atilano (European Journal of Taxonomy, 2021)
The unique Neotropical species of the alderfly genus Protosialis van der Weele, 1909, P. bifasciata (Hagen, 1861), is herein transferred to the newly described genus Caribesialis gen. nov. This new taxon is proposed to be sister to the clade Protosialis + Sialis Latreille, 1802, after a phylogenetic analysis that included male genital characters scored on a previous morphological matrix of the family. Also, Ilyobius nigrocephalus sp. nov., a remarkable new species from Ecuador, is described and its phylogenetic position is discussed. Furthermore, Ilyobius bimaculatus (Banks, 1920) from Bolivia, known solely from the female holotype, is redescribed. Based on the present study, the Neotropical fauna of Sialidae is proposed to be constituted by two genera, one insular (Cuba) and one continental (Mexico to Chile and Argentina).